Tieffrequente Geräusche in der Windenergieanlagentechnik. - Bunk, Oliver; Hoffmeier, Jörn (Springer-VDI-Verl., 2007)
Im Bereich der Erneuerbaren Energien findet die Windenergie in Deutschland mittlerweile große Verbreitung. Mit der fortschreitenden technologischen Entwicklung und der damit verbundenen zunehmenden Größe der Windenergieanlagen (WEA) wachsen auch die Kritikpunkte an der Technik. Einer davon ist die von WEA ausgehende Geräuschimmission. Neben dem eigentlich hörbaren Schall wird oftmals auch von Schall im nicht hörbaren Bereich, dem Infraschall, gesprochen. Schall im Frequenzbereich oberhalb des Infraschalls bis zu f = 90 Hz wird tieffrequenter Schall genannt. Im Zuge von mittlerweile mehreren durchgeführten Messungen bezüglich der Abstrahlung und Ausbreitung tieffrequenten Schalls bei Einzelanlagen oder Windparks (WIP) und gemäß DIN 45680 kann u. E. gesagt werden, dass die bislang gemessenen WEA i. d. R. keine tieffrequenten Geräusche abstrahlten. Die tieffrequente Lärmwirkung von WEA konnten gemäß DIN 45680 sehr gut bewertet werden. Offene Fragen hinsichtlich einer endgültigen Handhabung und der Beurteilungbleiben allerdings noch bestehen. difu

Within the field of the renewable energies the wind energy finds meanwhile a large spreading in Germany. Accompanied with the progressive technological development and the associatively increasing size of the wind energy plants (WEA), the points of criticism at this technology are growing too. One of these points is the noise immission from the wind energy plants. Apart from the really audible sound a normally inaudible sound in the low-frequency range is often mentioned, called infrasound. Sound in a frequency range above infrasound up to f = 90Hz is called low-frequency sound. Meanwhile after several accomplished measurements regarding the low-frequency sound radiation and propagation with single wind energy plants or wind farms and according to DIN 45680 it can be said, that the WEA, measured so far, didn t radiate low-frequency noise usually. Here plants with rated outputs in the order from Pel = 500 kW to 2.0 MW and with hub heights from h = 50 m to 100 m are investigated. In the rare cases, in which low-frequency noise occurred and could be measured, constant noise was found having no temporal fluctuations and no modulation. Therefore, it can be said, that the low-frequency noise effect of wind energy plants could be very well rated according to DIN 45680. Nevertheless regarding to a final handling and assessment open questions still exist.
Low-frequent noises in the technology of the wind enegry plants.
Keywords: Umweltschutz; Windenergie; Windenergieanlage; Lärm; Lärmemission; Lärmschutz; Schall; Windpark; Geräuschimmission